Multiple cargo deliveries of growth factors and antimicrobial peptide using biodegradable nanopolymer as a potential wound healing system - Vijayan A (Dove Medical Press, 2019)
Amritha Vijayan, Pinky Prabha James, CK Nanditha, GS Vinod Kumar Chemical Biology, Nano Drug Delivery Systems (NDDS), Bio-Innovation Center (BIC), Rajiv Gandhi Centre for Biotechnology, Thiruvananthapuram, Kerala 695014, India Background: Treatment of wounds with the help of nanoparticles (NPs) is more effective and superior in comparison to traditional wound healing methods as it protects and sustains active drug release at the wound site thus enhancing the safety of the drug and reducing the possibility of side effects. The advantages of this method are the possibility of allowing a reduction in administered dose, limiting toxicity levels to the minimum, and increasing safety of topical delivery of the drug.Materials and methods: We report the synthesis of a novel poly (lactic-co-glycolic acid) (PLGA) NP-based multicargo delivery system for growth factors and antimicrobial peptide. Growth factors vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) were entrapped in PLGA NPs by solvent diffusion method and an antimicrobial peptide (K4) was conjugated to the NP by carbodiimide chemistry. The developed multiple cargo delivery systems with growth factors (VEGF and bFGF) and an antimicrobial peptide (K4) were investigated and optimized for potential wound healing.Results: The system showed a sustained release of growth factors and was evaluated for cytotoxicity by MTT and live/dead assay, which revealed that the bioactivity of the growth factor-entrapped NPs was higher than that of free growth factors, and it also induced enhanced cell proliferation in vitro.Conclusion: The development of a system for the codelivery of growth factors (VEGF and bFGF) and an antimicrobial peptide (K4) was investigated for potential wound healing application. The entrapment of growth factors with very high efficiency is an advantage in this method along with its sustained release from the nanoparticulate system, which will enhance the angiogenesis. Our system also displayed broad-spectrum antimicrobial activity against both gram-positive and gram-negative bacteria. Keywords: growth factors, VEGF, bFGF, PLGA, antimicrobial peptides